Improving Early Reading Skills Through Letter-Matching Games - Safitri, Mazda Leva Okta; Meilani Tirta Sari; Abdulah; Ilham Arya Susanto; Nurdin Kamil (Journal of Practice Learning and Educational Development, 2026)
This study aimed to improve early reading skills and student activeness through the use of letter-matching games in Grade I of one public elementary school in Palembang City. The research employed a Classroom Action Research (CAR) design conducted in three cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 32 first-grade students. Data were collected through reading tests and observation sheets to measure students’ early reading abilities and learning activeness. The results showed a significant improvement in both early reading skills and student activeness across the three cycles. In Cycle I, the average reading score was 66.6 with a mastery percentage of 34%, and student activeness reached 63.4%. In Cycle II, the average score increased to 90.71 with a mastery percentage of 87%, while student activeness rose to 94%. In Cycle III, the average score further improved to 92.12 with a mastery percentage of 90%, and student activeness reached 96%. These results exceeded the predetermined success indicators, which required at least 80% of students to achieve mastery and a minimum of 75% student activeness. The findings indicate that the use of letter-matching games is effective in enhancing early reading skills and increasing student activeness. Therefore, letter-matching games can be recommended as an engaging and effective instructional strategy for early reading instruction in elementary schools.